2018
DOI: 10.1038/s41598-018-24751-y
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals genes involved in flavonoid biosynthesis and accumulation in Dendrobium catenatum From Different Locations

Abstract: In this study, we applied transcriptome and UHPLC-MS technologies to investigate the flavonoids and their biosynthesis- and accumulation-related genes in Dendrobium catenatum from three different locations. Eight flavonoid glycosides were identified using standard references or previously isolated substances with MS data analysis. The total flavonoid contents were determined by reagents, and all the data were analyzed. In total, 23139 unigenes were obtained using the Dendrobium catenatum genome data. Of these,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 56 publications
0
54
0
Order By: Relevance
“…Lam et al found that CYP75B4 and CYP93G1 promote tricin accumulation in Arabidopsis and O. sativa, which functions in generating 3′-hydroxylated flavonoids and flavone aglycones [56,57]. Recently, Lei et al found that a group of CYPs, including members of CYP71/72/77/78/81/85/86/ 90/93, were differentially expressed in Dendrobium catenatum from different locations and with different outlooks, which might be related to flavonoid biosynthesis [58]. CYP86 has been reported to be involved in suberin monomer biosynthesis in Arabidopsis [59].…”
Section: Discussionmentioning
confidence: 99%
“…Lam et al found that CYP75B4 and CYP93G1 promote tricin accumulation in Arabidopsis and O. sativa, which functions in generating 3′-hydroxylated flavonoids and flavone aglycones [56,57]. Recently, Lei et al found that a group of CYPs, including members of CYP71/72/77/78/81/85/86/ 90/93, were differentially expressed in Dendrobium catenatum from different locations and with different outlooks, which might be related to flavonoid biosynthesis [58]. CYP86 has been reported to be involved in suberin monomer biosynthesis in Arabidopsis [59].…”
Section: Discussionmentioning
confidence: 99%
“…Dendrobium catenatum (D. officinale), a perennial herb in the Orchidaceae, is rich in flavonoid glycosides 24 and is mainly distributed in Southeast, South, and Southwest China 25 . In the wild, D. catenatum largely grows year round on cliffs that receive abundant sunlight and scant water 26 . Owing to its high medicinal value, D. catenatum has been widely used in traditional Chinese medicine 27 .…”
Section: Introductionmentioning
confidence: 99%
“…According to Chinese medical theory, the stems of D. catenatum can nourish yin, enhance gastric motility, and increase body fluids regulating immunity 28 . Modern pharmacological studies have shown that the active ingredients of D. catenatum include polysaccharides 29 , flavonoids 26 , and bibenzyls 30 , which promote salivation and relieve the symptoms of diabetes 31,32 .…”
Section: Introductionmentioning
confidence: 99%
“…Other than anthocyanins, colored flavonoid glycosides contribute to the diversity of colors in fruits and flowers [ 13 ]. To date, only one study has qualitatively or quantitatively assessed the flavonoids from D. officinale [ 23 ]. The flavonoids in green and red D. officinale stems were detected by UPLC-PDA-QTOF-MS ( Table S1 ).…”
Section: Resultsmentioning
confidence: 99%